RADEC-Based Teaching Module Assisted by Media Gallery Walk on Oral Communication Skills: A Development Study - Nadiroti Muslihah, Neni; Nuriyanti, Risma; Sukma Nugraha, Widdy (IJORER : International Journal of Recent Educational Research, 2026)
Objective: The background of this study is based on the importance of learning that encourages active participation of prospective teachers and oral communication skills in accordance with current curriculum requirements. The RADEC model was chosen because it is able to facilitate a systematic and structured learning process, while the Gallery Walk media was used to increase interaction between prospective teachers and provide space for active presentation of work results. The purpose of this study was to determine the development of teaching modules based on the RADEC learning model assisted by the Gallery Walk media on oral communication skills for prospective elementary school teachers. The design used was the ADDIE model, which was limited to three stages, namely analysis, design, and development. The research data was obtained from the validation of materials and media, as well as from a questionnaire responded to by prospective teachers. The results showed that the teaching module based on the RADEC learning model assisted by the Gallery Walk media obtained an average score of 93.1 from subject matter experts, which is classified as very feasible, and an average score of 90.2 from learning media experts, which is also classified as very feasible. Based on these two scores, the average score was 91.7, which is in the very feasible categoryThese results indicate that the RADEC-based teaching module assisted by Gallery Walk media for prospective elementary school teachers is feasible to be used as a learning resource for introducing various learning models. The novelty of this study lies in the explicit integration of the structured RADEC stages (Read, Answer, Discuss, Explain, Create) with the interactive Gallery Walk activity. Unlike previous interventions that mainly rely on discussions or presentations, this combination systematically develops students’ oral communication skills through progressive learning stages and visual–collaborative interaction. The Gallery Walk component allows students to present ideas, observe peers’ work, and provide feedback, creating a more interactive and reflective learning experience. Thus, this module offers a distinctive pedagogical approach to strengthening prospective teachers’ oral communication skills.